Anti-proliferative effects of a polyherbal formulation on HL-60, HCT-116, and HeLa cell lines: a docking simulation and response surface design-aided study - Egbuna, Chukwuebuka; Patrick-Iwuanyanwu, Kingsley C.; Onyeike, Eugene N.; Khan, Johra; AlDosari, Sahar; Jahan, Sadaf; Adedokun, Kamoru A.; Imodoye, Sikiru O.; Bello, Ibrahim O.; Uche, Chukwuemelie Z.; Noreen, Sana; Ifemeje, Jonathan C. (Frontiers in Chemistry, 2025)
Cancer is a complex global health challenge that requires novel and holistic approaches to treatment and prevention. Polyherbal medicines, composed of multiple plants with historical use in traditional medicine, have gained popularity due to their safety, cost-effectiveness, and accessibility. However, selecting the right plants and determining optimal combinations for enhanced biological effects remains challenging. To address this, a molecular docking study was conducted, targeting proteins implicated in cancer pathogenesis. The study identified bioactive compounds with strong binding energies, guiding the selection of polyherbal formulations for further experimentation. Using response surface methodology, various combinations of plant extracts were screened for their antioxidant properties and phytochemical content. Among the formulations tested, PHEE (Polyherbal Ethanolic Extract), comprising 70% soursop leaf, 5% jackfruit leaf, 5% orange peel, 15% citrus juice, and 5% apple fruit ethanolic extracts, exhibited the most potent biological activities, followed by SLEE (Soursop Leaf Ethanolic Extract), a 100% soursop leaf ethanolic extract. Design Expert Software predicted soursop leaf extract as a key contributor to desirable outcomes, attributed to its rich phytochemical composition. Cell-based assays revealed varying cytotoxic effects of the extracts on leukemia cells, with PHEE showing the highest potency (IC50 = 2.50 μg/mL), followed closely by SLEE (IC50 = 2.90 μg/mL). These effects are potentially due to the abundant acetogenins and flavonoids present in the extracts. However, caution is warranted regarding their cytotoxicity to normal cells. Apoptotic studies confirmed the ability of both PHEE and SLEE to induce programmed cell death, further supporting their potential as anticancer agents. This research underscores the importance of strategic plant combinations in polyherbal formulations and highlights PHEE as a promising candidate for further investigation in cancer treatment.